2008
DOI: 10.1124/mol.108.051623
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Trafficking of G Protein-Coupled Receptors: Function of the C-Terminal F(X)6LL Motif in Export from the Endoplasmic Reticulum

Abstract: We have reported previously that the F(X) 6 LL motif in the C termini is essential for export of ␣ 2B -adrenergic (␣ 2B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(116 citation statements)
references
References 39 publications
6
110
0
Order By: Relevance
“…These treatment conditions are known to promote the cell surface expression of certain misfolded proteins by virtue of either relaxing the quality control system or promoting tighter protein conformations within the ER. We have previously demonstrated that the residue Phe-436 modulates ␣ 2B -AR folding likely through intramolecular interactions with other hydrophobic residues such as Val-42 in the first transmembrane domain (25) and thus it was used as a positive control. HEK293 cells were transfected with ␣ 2B -AR, ␣ 2B -AR mutant F436A, AT2R, or AT2R mutant ExD-AxA and then either treated with DMSO, PD123319 or cultured at 30°C.…”
Section: The Di-acidic Exd Motif Is Unlikely Involved In Proper At2rmentioning
confidence: 99%
See 4 more Smart Citations
“…These treatment conditions are known to promote the cell surface expression of certain misfolded proteins by virtue of either relaxing the quality control system or promoting tighter protein conformations within the ER. We have previously demonstrated that the residue Phe-436 modulates ␣ 2B -AR folding likely through intramolecular interactions with other hydrophobic residues such as Val-42 in the first transmembrane domain (25) and thus it was used as a positive control. HEK293 cells were transfected with ␣ 2B -AR, ␣ 2B -AR mutant F436A, AT2R, or AT2R mutant ExD-AxA and then either treated with DMSO, PD123319 or cultured at 30°C.…”
Section: The Di-acidic Exd Motif Is Unlikely Involved In Proper At2rmentioning
confidence: 99%
“…Similar to many other plasma membrane proteins, GPCR export from the ER is a key event in the anterograde trafficking to the cell surface (17)(18)(19)(20). Indeed, ER export has been shown to be a rate-limiting step for the cell surface transport of the receptors (21) and a number of studies have recently identified highly conserved hydrophobic sequences, which are required for GPCR export from the ER to the cell surface (22)(23)(24)(25)(26)(27). Although the molecular mechanism underlying the function of these motifs in controlling GPCR export remains elusive, several studies suggest that they are likely involved in the regulation of proper receptor folding in the ER.…”
mentioning
confidence: 99%
See 3 more Smart Citations